Imaging with ultra-small-angle X-ray scattering using a Laue-case analyzer and its application to human breast tumors. (December 2017) - Shimao, Daisuke; Sunaguchi, Naoki; Sasaya, Tenta; Yuasa, Tetsuya; Ichihara, Shu; Kawasaki, Tomonori; Ando, Masami
Highlights: We developed USAXS imaging using a Laue-case analyzer. We acquired USAXS images of breast tumor specimens. USAXS imaging can extract closely packed scattering bodies in a specimen. Sensitivity can be controlled by changing the threshold level of the rocking curve. A fusion image is useful for studying USAXS image. Abstract: Purpose: In this study, we demonstrate a novel imaging technique, based on ultra-small-angle X-ray scattering (USAXS) that uses a Laue-case Si wafer as the angle analyzer. Methods: We utilized the (1 1 1) diffraction plane of a 356 μm thick, symmetrically cut Si wafer as the angle analyzer, denoted by A[L]. With this device, we performed USAXS imaging experiments using 19.8 keV synchrotron X-rays. The objects we imaged were formalin-fixed, paraffin-embedded breast tumors (an invasive carcinoma and an intraductal papilloma). During image acquisition by a charge-coupled device (CCD) camera, we varied the rotation angle of the analyzer in 0.02″ steps from −2.40″ to +2.40″ around the Bragg angle. The exposure time for each image was 2 s. We determined the amount of ultra-small-angle X-ray scattering from the width of the intensity curve obtained for each local pixel during the rotation of the analyzer. Results: We acquired USAXS images of malignant and benign breast tumor specimens using the A[L] analyzer; regions with larger USAXS form brighter areas in the image. We varied the sensitivity of the USAXS image by changing the threshold level of the object rocking curve. Conclusions: The USAXS images can provide information about the internal distribution of closely packed scattering bodies in a sample with reasonable sensitivity. This information differs from that obtainable through refraction-contrast imaging. Although further validation studies will be necessary, we conclude that USAXS imaging using a Laue-case analyzer may have significant potential as a new diagnosis technique.